2009
DOI: 10.1073/pnas.0804177106
|View full text |Cite
|
Sign up to set email alerts
|

Rb/Cdk2/Cdk4 triple mutant mice elicit an alternative mechanism for regulation of the G 1 /S transition

Abstract: The G1/S-phase transition is a well-toned switch in the mammalian cell cycle. Cdk2, Cdk4, and the rate-limiting tumor suppressor retinoblastoma protein (Rb) have been studied in separate animal models, but interactions between the kinases and Rb in vivo have yet to be investigated. To further dissect the regulation of the G 1 to S-phase progression, we generated Cdk2 ؊/؊ Cdk4 ؊/؊ Rb ؊/؊ (TKO) mutant mice. TKO mice died at midgestation with major defects in the circulatory systems and displayed combined phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 42 publications
3
27
0
Order By: Relevance
“…Ink4a expression cooperatively blocks the activation of both cyclin D kinase (CDK4/6) and cyclin E kinase (CDK2), allowing the accumulation of the dephosphorylated form of the retinoblastoma tumor suppressor protein (pRb) and thereby causing permanent cell cycle arrest (7)(8)(9)(10). It has become apparent that cellular senescence can be induced by a variety of potentially oncogenic stimuli, such as telomere shortening, DNA damage, oxidative stress, or oncogene expression (11)(12)(13)(14), suggesting that cellular senescence is likely to act as a tumor suppression mechanism in vivo (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Ink4a expression cooperatively blocks the activation of both cyclin D kinase (CDK4/6) and cyclin E kinase (CDK2), allowing the accumulation of the dephosphorylated form of the retinoblastoma tumor suppressor protein (pRb) and thereby causing permanent cell cycle arrest (7)(8)(9)(10). It has become apparent that cellular senescence can be induced by a variety of potentially oncogenic stimuli, such as telomere shortening, DNA damage, oxidative stress, or oncogene expression (11)(12)(13)(14), suggesting that cellular senescence is likely to act as a tumor suppression mechanism in vivo (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…As we expected, this drug induces p16 expression by unknown mechanism. It could be through activation of Rb, which activates p16 (18,19), or may be through p16 demethylation that results in increasing p16 expression (20). Hence, further work should be performed to determine the exact mechanism by which p16 is up regulated by bafetinib.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, the involvement of Cdk1 in S phase may have been underestimated mainly because the low levels of active Cdk1 compared to the high levels of Cdk2 during DNA replication suggested that Cdk2 was predominant over Cdk1 at this step of the cell cycle (Bashir and Pagano, 2005). In this emerging picture of the cell cycle regulation, these new data probably did not profoundly affect the roles that were initially attributed to the different Cdk/cyclin complexes but rather introduce the notion of redundancy and flexibility (Li et al, 2009b;Satyanarayana and Kaldis, 2009b (Li et al, 2009a;Malumbres et al, 2004;Satyanarayana and Kaldis, 2009b). These deletions did not affect early embryogenesis demonstrating multiple compensatory mechanisms and overlapping roles of these genes.…”
Section: Are Cdk/cyclin Complexes Functionally Redundant To Phosphorymentioning
confidence: 97%